Self-Efficacy, Religiosity, and Social Support with Undergraduate Students' Self-Regulated Learning in Distance Learning - Munandar, Muhammad; Ruhaena, Lisnawati (Journal An-Nafs: Kajian Penelitian Psikologi, 2023)
The existence of a pandemic has limited all sectors of activity, one of which is the education sector. In March 2020, distance learning began to be implemented in Indonesia, where students experienced problems during the implementation. The sample was undergraduate students participating in distance learning. This study used quantitative research with the correlational research design with multiple regression analysis involving 408 students participating in distance learning. The motivated Strategy for Learning Questionnaire (MSLQ) was used to measure self-regulated learning, the General Self-Efficacy Scale (GSES) was used to measure self-efficacy, the Centrality of Religiosity Scale (CRS) was used to measure religiosity, and the parental social support compiled by Fitrotin was used to measure parental social support. Data analysis used linear regression. The results of the study revealed that self-efficacy, religiosity, and parental social support had a relationship with self-regulated learning. This is indicated by a positive Beta = 8.590, a p-value of 0.001 (p <0.005), a regression (F value) of 97.176, and an effective contribution to self-regulated learning of 41.9%. Programs to increase self-efficacy, religiosity, and parental social support are very important to increase self-regulated learning.